Politeness Strategies in Directive Speech Act in The Greatest Showman (2017) Movie - Monika Tagugurad; Nur Rosita (Universitas Negeri Padang, 2023)
Language as a means of communication always develops overtime. The value of politeness implied in the language. Furthermore, in interpreting the politeness value of a language, situational context has strong function to be considered. This cannot be separated from the speakers’ ways to express language with the politeness standard so that impact the listener's tendency to interpret the politeness value without seeing the situation affects it. The research purpose is to find out the types of politeness strategies and situational context that affects it in directive speech act in the Greatest Showman movie script. The researcher use qualitative method. The result was the five politeness strategies namely bald on record 42 data (29 %), positive politeness 61 (42 %), negative politeness 34 data (23 %), and bald off record 8 (6 %) where in each of these politeness strategies the component of speech appears as a situational context that influences. Additionally, the result show that the movie illustrates The Greatest showman movie as a motivational contains more positive politeness strategy which relates to the movie background that occurred in 19th century society, it is still valuable to uphold family values and respect for others according to their social class.